Bidirectional Association Between Asthma and Obesity During Childhood and Adolescence: A Systematic Review and Meta-Analysis - Li-Shen Shan; Qian-Lan Zhou; Yun-Xiao Shang (Frontiers Media S.A., 2020)
Objective: Co-occurrence of pediatric asthma and obesity has been widely reported, yet the causal directions between these two disorders are still not well-understood. The objective of this meta-analysis is to explore whether there is a possibility of a bidirectional association for these two disorders in children and adolescents.Methods: PubMed, Embase, Web of Science, and CENTRAL databases were searched up to August 2020. Cohort studies reporting the associations of obesity with risk of physician-diagnosed asthma or physician-diagnosed asthma with risk of obesity in children and adolescents were eligible for the review.Results: A total of 3,091 records were identified from the four databases, with final inclusion of nine. Six studies reported the association between obesity and risk of asthma; three studies reported the association between asthma and risk of childhood obesity. As evaluated by the Newcastle-Ottawa quality assessment scale, all studies were assessed as high-quality studies. There was a statistically significant association between obesity and increased risk of physician-diagnosed asthma in children and adolescents. The pooled RR was 1.39 (95% CI: 1.28, 1.50; p < 0.001), with significant heterogeneity across studies (I2 = 81.7%; pheterogeneity < 0.001). The pooled RR in boys was 1.53 (95% CI: 1.17, 1.99; p = 0.002), but such a significant association was not observed in girls (RR = 1.17, 95% CI: 0.79, 1.72; p = 0.434). For the association of asthma with risk of childhood obesity, the pooled RR was 1.47 (95%CI: 1.25, 1.72; p < 0.001) without statistical heterogeneity (I2 = 0%, pheterogeneity = 0.652).Conclusion: There is a bidirectional association between obesity and asthma during childhood and adolescence, suggesting that childhood obesity drives an increase in the onset of asthma; meanwhile, childhood asthma may also increase risk of obesity for children and adolescents.